Shrinkage of mortars with a suspension of superabsorbent polymers - Ribeiro, A. C. (2010)
The use of superabsorbent polymers (SAP) is effective in controlling internal desiccation of cementitious materials with low W/C. Until now, the use of this type of products is limited to research and special applications. The spread of the use on concrete for current applications depends on economy considerations and ease of application. A sample of a suspension of SAP, which is easy to incorporate in concrete production, was supplied by a large producer, containing 3 % of polymer. Autogenous shrinkage, total shrinkage, mass loss and compressive strength tests were performed in mortars with W/C=0.325 and W/C=0.42, with and without SAP. Results indicate that, if sufficient amount of the suspension is used, the admixture is useful for controlling early age shrinkage, but no benefits are evident for total shrinkage at 28 days, and a decrease of compressive strength is observed.